THE EFFECT OF FINANCIAL LEVERAGE, PROFITABILITY, AND INSTITUTIONAL OWNERSHIP TOWARDS INCOME SMOOTHING IN BASIC INDUSTRY AND CHEMICAL, MISCELLANEOUS INDUSTRY, AND CONSUMER GOODS INDUSTRY LISTED ON INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2021 - Nurainun Bangun; Justin (INQUISITIVE : International Journal of Economic, 2023)
The purpose of this study is to obtain empirical evidence about the effect of financial leverage, profitability, and institutional ownership towards income smoothing in basic industry and chemical, miscellaneous industry, and consumer goods industry listed on Indonesia Stock Exchange for the period 2019-2021. This study used 65 samples and 195 data from companies in basic industry and chemical, miscellaneous industry, and consumer goods industry that have been selected using purposive sampling technique. The data was processed using Eviews version 12 software. The result of this study shows that financial leverage and profitability have significant negative effect towards income smoothing, while institutional ownership has no effect towards income smoothing.